Editorial: Platelets and Immune Responses During Thromboinflammation - Schattner, Mirta Ana (2020)
The word thromboinflammation appeared in 2004 to describe the interactions and cooperation between platelets and neutrophils in the context of arterial in-stent restenosis (1). Almost two decades later, multiple sources of evidence clearly show that the interplay between thrombosis and inflammation involves several pathways and occurs in various pathophysiological situations such as sepsis, disseminated intravascular coagulation (DIC), stroke, cancer, stress and rheumatoid arthritis, among others. Thromboinflammation is driven by mutual interactions and reciprocal activation between endothelial cells, subendothelium, leukocytes, platelets, and the humoral innate immune system, involving the complement, coagulation, and fibrinolytic signaling cascades.